Removal of hexanal in cooking fume by combination of storage and plasma-catalytic oxidation on alkali-modified Co-Mn solid solution - Yao, Xin; Gao, Mengxiang; Wei, Zhidong; Chen, Mingxia; Shangguan, Wenfeng (Chemosphere (Oxford), 2019)
Cooking oil fumes as an important source of volatile organic compounds in metropolitan areas are poisonous to the environment and human health. In this study, the removal of hexanal (a representative of cooking fume) using “storage-plasma catalytic oxidation” at ambient conditions has been investigated. Alkali-modified Co-Mn catalysts were synthesized by coprecipitation method and further characterized by XRD, SEM, N2 adsorption–desorption, H2-TPR, O2-TPD and XPS techniques. It was clearly shown that the Na modification afforded a remarkable enhancement in the hexanal storage capacity, which is ascribed to the formation of surface hydroxyls that resulted in the chemical adsorption. Moreover, the plasma-catalytic oxidation results showed 99.4% hexanal removal and 85.7% CO2 selectivity at a GHSV of 47700 h−1. XPS results revealed that Na modification promoted the formation of more abundant Co3+, Mn3+ cations and surface adsorbed oxygen species, thus facilitated the oxidation process. In-situ FTIR results revealed that Na modification could trigger disproportionation reaction, resulting in the transformation of adsorbed hexanal into alcohol and carboxylic acid thus further speeds up the oxidation rate. This work provides a low-cost, highly efficient and energy-consuming approach for the removal of gaseous cooking fume by storage and plasma catalytic oxidation cycle at room temperature. Na modification led to the formation of hydroxyl group, promoted chemical adsorption of hexanal, thus facilitated the catalytic oxidation reaction. [Display omitted] •Alkali-modified Co-Mn solid solution catalysts were successfully prepared by coprecipitation method.•CoMn-Na shows superior hexanal storage capacity due to the surface hydroxyls that resulted in the chemical adsorption.•Disproportionation of hexanal into alcohol and carboxylic acid further speeds up the oxidation rate.•The “storage-plasma oxidation” system offers a highly efficient and energy-consuming approach for VOCs removal in the cooking fume.